Biofilm Formation and Degradation of Commercially Available Biodegradable Plastic Films by Bacterial Consortiums in Freshwater Environments - Morohoshi, Tomohiro; Oi, Taishiro; Aiso, Haruna; Suzuki, Tomohiro; Okura, Tetsuo; Sato, Shunsuke (Microbes and Environments, 2018)
We investigated biofilm formation on biodegradable plastics in freshwater samples. Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) was covered by a biofilm after an incubation in freshwater samples. A next generation sequencing analysis of the bacterial communities of biofilms that formed on PHBH films revealed the dominance of the order Burkholderiales. Furthermore, Acidovorax and Undibacterium were the predominant genera in most biofilms. Twenty-five out of 28 PHBH-degrading isolates were assigned to the genus Acidovorax, while the other three were assigned to the genera Undibacterium and Chitinimonas. These results demonstrated that the order Burkholderiales in biofilms functions as a degrader of PHBH films.